Um estudo sobre a qualidade de vida no trabalho de docentes que exercem cargos administrativos em uma instituição federal de ensino - Araújo, Marina Farias de (2022)
The work and complex activities developed by higher education professor have been the object of analysis and investigation by researchers, mainly after the expansion of higher education (which has taken place in recent decades) and by the transformations of socioeconomic and technological nature. In Brazil, it is common for university professors to assume administrative positions without prior training and technical guidance regarding the activities and management attributions they will exercise, that is, in general, the training of professors is marked by some gaps, especially in terms of related to university management. In addition, the Covid-19 pandemic has caused significant changes in the personal, political, socioeconomic, cultural areas, etc. For professors at Higher Education Institutions (HEIs), one of these transformations involved social distancing measures and the need to resignify/redesign their professional practices, that is, teaching. In this way, it was also verified the need to investigate the impacts of the emergency remote work for these teaching professionals. The aim of this study was identifying how performance in administrative/management positions affects health and perceptions of Life Quality at Work (LQW) of UFMT professors. It is a mixed method descriptive and explanatory research (quantitative and qualitative) divided in two stages: A) data collection carried out through an online questionnaire with items related to sociodemographic/professional profile; questions about (dis)satisfaction with emergency remote work/teaching; and the Life Quality instruments in the Total Work (TQWL-42) and the Multifunctional Work-Family Conflict Scale (EMCT-F). B) conducting online semi-structured interviews. For data quantitative analysis (first step), we used simple descriptive analysis and inferential analysis (correlation and regression). As for the qualitative analysis of the data (second step) the content analysis method was used for the categorization/analysis of research data. The participants in this study were the permanent active professors at the Federal University of Mato Grosso (UFMT). The step of quantitative analysis considered the data of 290 professors who participated in the analysis's simple descriptions; 220 professors composed the sample of inferential analyses. Nine professors who hold paid administrative positions participated in the qualitative (interviews). The analysis of the results shows that assuming administrative positions procedures entails significant changes in the professor's work routine, thus impacting on health and on the perception of LQW. Regarding emergency remote work/teaching , the dissatisfaction of teachers with such a modality of work was evident , as they report a worsening of working conditions. Note that the public universities need to invest in LQW policies aimed at managing professors, given that such initiatives will contribute to the improvement of these professionals’ performance and, consequently, an increase in the level of health and LQW, as well as will be able to provide good services to the population.